Copy number variants calling from WES data through eXome hidden Markov model (XHMM) identifies additional 2.5% pathogenic genomic imbalances smaller than 30 kb undetected by array‐CGH. (9th February 2022) - Tisserant, Emilie; Vitobello, Antonio; Callegarin, Davide; Verdez, Simon; Bruel, Ange‐line; Aho Glele, Ludwig Serge; Sorlin, Arthur; Viora‐Dupont, Eleonore; Konyukh, Marina; Marle, Nathalie; Nambot, Sophie; Moutton, Sébastien; et al.
Abstract: It has been estimated that Copy Number Variants (CNVs) account for 10%–20% of patients affected by Developmental Disorder (DD)/Intellectual Disability (ID). Although array comparative genomic hybridization (array‐CGH) represents the gold‐standard for the detection of genomic imbalances, common Agilent array‐CGH 4 × 180 kb arrays fail to detect CNVs smaller than 30 kb. Whole Exome sequencing (WES) is becoming the reference application for the detection of gene variants and makes it possible also to infer genomic imbalances at single exon resolution. However, the contribution of small CNVs in DD/ID is still underinvestigated. We made use of the eXome Hidden Markov Model (XHMM) software, a tool utilized by the ExAC consortium, to detect CNVs from whole exome sequencing data, in a cohort of 200 unsolved DD/DI patients after array‐CGH and WES‐based single nucleotide/indel variant analyses. In five out of 200 patients (2.5%), we identified pathogenic CNV(s) smaller than 30 kb, ranging from one to six exons. They included two heterozygous deletions in TCF4 and STXBP1 and three homozygous deletions in PPT1, CLCN2, and PIGN . After reverse phenotyping, all variants were reported as causative. This study shows the interest in applying sequencing‐based CNV detection, from available WES data, to reduce the diagnostic odyssey of additional patients unsolved DD/DI patients and compare the CNV‐detection yield of Agilent array‐CGH 4 × 180kb versus whole exome sequencing.